Assessment of Adequacy of Dialysis in Patients Undergoing Dialysis with Bicarbonate Solution - Raheleh Mohseni; Ehteram Sadat Ilali (Tehran University of Medical Sciences, 2012)
Background & Aim: Hemodialysis is a common replacement therapy for patients with ESRD, worldwide. Effective and adequate hemodialysis can improve quality of life and reduce complications of renal failure. Enhancing quality of dialysis results in reducing the complications and mortality rate in patients with chronic renal failure. The aim of this study was to assess the adequacy of dialysis in patients undergoing dialysis with Bicarbonate solution in hemodialysis ward of a hospital in Sary. Methods & Materials: This cross-sectional study was conducted on 50 patients admitted in the hemodialysis ward with chronic renal failure diagnosis. A researcher-made questionnaire was used to gather data. The KT/V formula was used to assess the adequacy of hemodialysis. The URR common characteristic was also measured. Data were analyzed using statistical tests. Results: The mean age of patients was 54.76±12.55 years. The mean of KT/V and URR were 0.26±0.92 and 0.47±0.09, respectively. The kt/v ratio was lower than 1.2 in 85.2% of the patients and the URR was lower than 65% in 97.8% of the patients. Conclusion: The hemodialysis adequacy was low in 85.2% of the patients in the hospital and the hemodialysis efficacy indicators were lower than the standard measures. Assessment to find the reasons of low efficacy of hemodialysis is recommended.